2017
DOI: 10.1002/mame.201700300
|View full text |Cite
|
Sign up to set email alerts
|

Pore Size Distribution and Blend Composition Affect In Vitro Prevascularized Bone Matrix Formation on Poly(Vinyl Alcohol)/Gelatin Sponges

Abstract: This study aims at identifying compositional and architectural (pore size and distribution) parameters of biocompatible scaffolds, which can be best suitable for both osteoblasts and endothelial cells to produce optimized 3D cocultured constructs. Spongy scaffolds are prepared using poly(vinyl alcohol) (PVA) and gelatin (G) at different weight compositions (PVA/G range: 100/0â\u80\u9350/50, w/w) via emulsion and freeze-drying. The higher the gelatin content, the larger is the volume occupied by higher size por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…We investigated the protective effect of OLE from Tuscan olive trees on endothelial cells, using a conventional culture (2D model) and a novel tissue-engineered culture (3D model) of HUVECs. Our past work has, in fact, highlighted the importance of scaffold architecture in generating complex vascularized in vitro models using HUVECs [29]. In this study, a new 3D model was obtained by fabricating a fiber mesh of P(VDF-TrFE), a biocompatible polymer used for biomedical devices and tissue engineering [30].…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the protective effect of OLE from Tuscan olive trees on endothelial cells, using a conventional culture (2D model) and a novel tissue-engineered culture (3D model) of HUVECs. Our past work has, in fact, highlighted the importance of scaffold architecture in generating complex vascularized in vitro models using HUVECs [29]. In this study, a new 3D model was obtained by fabricating a fiber mesh of P(VDF-TrFE), a biocompatible polymer used for biomedical devices and tissue engineering [30].…”
Section: Discussionmentioning
confidence: 99%
“…Polymers are one of the most common materials that have been used for fabrication of tissue engineering scaffolds. Natural polymers (collagen, gelatin, chitosan, etc.) have shown more similarity to the composition of the body following better interaction with cells .…”
Section: Introductionmentioning
confidence: 99%
“…Co-cultures of MSCs and endothelial precursor cells have demonstrated that these different cell populations have a synergistic action. Indeed, studies where MSCs and EPCs or human umbilical vein cells (HUVECs) were co-cultured on 3D scaffolds have shown an improvement in the survival rate of MSCs and stimulation of bone differentiation as well as angiogenesis [ 98 , 99 , 100 , 101 ]. A schematic of MSC and HUVEC co-culture on a scaffold is reported in Figure 8 .…”
Section: Cell Sources Used To Engineer Vascularized Bone Substitutes and Cellular Susceptivity To (Piezo)electric Stimulimentioning
confidence: 99%
“… Schematic showing: ( A ) a fracture involving bone tissue including vasculature; ( B ) a porous scaffold; and ( C ) histological analysis displaying a pore colonized by a dual cell population: osteoblast-like cells producing mineral matrix (by von Kossa staining positive, in black), and endothelial cells surrounding the pore walls (von Kossa staining negative, in red), reprinted with permission and adapted from [ 101 ], under John Wiley and Sons Copyright Clearance Center (license number 5170741359741). …”
Section: Figurementioning
confidence: 99%